Managing subsidiary dynamics headquarters role, capability development and China strategy - Cheng, Joseph L. C. 1952-; Maitland, Elizabeth, 1972-; Nicholas, Stephen, 1946- (Advances in international management ;, 2009)
A major development in recent research on the multinational enterprise (MNE) is the increased attention given to the interdependent, differentiated roles of the subsidiaries and their implications for MNE and subsidiary management. Paralleling this development is the shift away from studying subsidiaries as subunits to be controlled by the headquarters to investigating what subsidiaries do and how their activities can help develop firm-specific advantages. This volume includes contributions from leading scholars in the field from North America, Europe, and Asia-Pacific. Different from the traditional, single-discipline based investigation, it presents a multi-disciplinary approach to researching subsidiary dynamics and its effective management, with a focus on three important issues: the role of the headquarters within the context of subsidiaries as members of a differentiated, interdependent network; the development of subsidiary capabilities and their impact on firm performance; and, subsidiaries as learning agents for the MNE, particularly in emerging markets such as China.